Novel earth-abundant and highly efficient electrocatalysts for hydrogen and oxygen production - Nsanzimana, Jean Marie Vianney (2019)
Hydrocarbon fuels are a primary source of energy worldwide, but this resource is quickly becoming depleted, and carbon dioxide emissions from burning said fuel contribute greatly to global warming. Alternative clean energy sources are thus required for the development of a sustainable environment and society. The so-called ‘hydrogen economy’ is a promising candidate to provide green and sustainable energy due to its high energy density and carbon-neutral fuel. Water electrolysis has recently gained much attention as an environmentally friendly technology for hydrogen production. However, the occurrence of oxygen evolution reaction (OER) at the anodic electrode of water electrolyzer, a thermodynamically uphill reaction exhibiting sluggish kinetics, severely limits the overall efficiency of water splitting. OER is a critical challenge to be considered, not only for water electrolysis but also for other energy storage and conversion technologies. Currently, the state-of-the-art catalysts for both hydrogen evolution reaction (HER) and OER are noble metal‐based materials. However, their high cost, poor long-term durability, and scarcity hinder application at an industrial scale. Thus, the development of economically viable materials for HER and OER is crucial and relevant to their easier deployment for large-scale applications in electrochemical energy storage and conversion technologies. In the first part of this dissertation, an earth-abundant and efficient oxygen-evolving electrocatalyst based on metal borides is presented. Amorphous nanoparticles were prepared by chemical reduction of metal ions with sodium borohydride in aqueous solution. This method allowed homogeneous incorporation of transition metals in nickel boride nanostructure which improved the electrochemical activity of the catalyst. The as-prepared metal boride materials outperformed the existing commercial precious metal-based catalyst (Ir/C) for OER and for overall water splitting. In addition, multimetallic borides outperformed monometallic borides due to the synergistic effect from well-distributed transition metal constituents. In the second part of this dissertation, an earth-abundant tungsten–nickel alloy electrocatalyst for superior hydrogen evolution was developed and deployed as an electrode without an organic binder. The electrode was prepared by a hydrothermal process followed by annealing in the presence of H2 environment. The as-prepared electrode displayed bifunctional application both for HER and OER. Owing to the excellent electrocatalytic performance arising from the synergistic effect of tungsten–nickel interaction through d-orbital electron transfer, the as-prepared material was comparable to some of the best tungsten-based HER electrocatalysts. The lower adsorption energy of water molecules and a small Gibbs free energy of hydrogen adsorption on tungsten atoms, as measured from DFT calculations, revealed favorable water electrolysis kinetics. Thirdly, in order to boost the electrochemical performance of unsupported metal borides studied in the first piece of work, a practical approach for incorporating metal boride nanosheets onto a highly conductive substrate is presented. The developed material displayed better oxygen evolution activity compared to the unsupported metal borides and advanced stability in harsh alkaline electrolytes. A synergistic effect between highly abundant catalytically active sites and the 3D porous substrate improved the electron transport arising from the presence of highly negative boron and the high conductivity of the substrate, resulting in an outstanding electrocatalytic activity. The results of this work showed an effective method to boost the electrochemical performance of metal borides by supporting them on a highly conductive substrate. Inspired by (1) the facile preparation of metal borides by reducing metal ions in aqueous solution as presented in the first and third parts, and (2) the possibility of reducing graphene oxide by the same reducing agent used in these experiments, a fast and simple method of synthesizing amorphous ternary metal borides while simultaneously reducing the graphene oxide (GO) sheets was developed in the fourth part of this thesis. The as-prepared hybrid material exhibited outstanding OER performance and stability as compared to the pristine catalyst of the same composition under prolonged OER operation. In 1.0 M KOH, only 230 mV was required to afford a current density of 15 mA cm–2 with a small Tafel slope of 50 mV dec–1. This electrocatalytic performance was also much better compared to the commercial RuO2 catalyst. DFT calculations suggested that the in situ formation of MOxHy during electrochemical activation acted as active sites for water oxidation. The superior OER activity of the as-prepared catalyst was attributed to (i) its unique amorphous structure to allow abundant active sites, (ii) synergistic effect of constituents, and (iii) strong coupling of active material and highly conductive rGO. Finally, the last chapter summarizes the results of these projects and proposes an outlook for future works based on them.